Chest HRCT versus RT-PCR for the Detection of COVID-19 in Bangladesh - Ghosh, Kona; Das, Shantanu (Jalalabad Medical Journal, 2025)
The coronavirus disease 2019 (COVID-19) pandemic is a crisis of a completely different magnitude, and it is a challenge to life in the whole world, including Bangladesh. The real-time reverse transcription polymerase chain reaction (RT-PCR) tests are currently the gold standard diagnostic tool for COVID-19. This observational study was done to evaluate the diagnostic assessment of high-resolution computed tomography (HRCT) of the chest as compared to a RT-PCR test in COVID-19 patients attending the Radiology and Imaging department of Jalalabad Ragib-Rabeya Medical College Hospital, Sylhet, from 1st July 2020 to 31st December 2021. This study included 387 patients admitted to the ICU and suspected of having COVID-19 who went to the radiology and imaging department for HRCT of the chest for the diagnosis of COVID-19 pneumonia. Simultaneously, nasal swabs from the same number of patients were tested by RT-PCR in the government-approved centre to diagnose COVID-19. Demographic and clinical data were collected by a structured questionnaire, and analysis was done with the help of the Statistical Package for Social Science (SPSS) version 23. Abnormal HRCT was discovered in 317 patients, 309 of whom were positive and 8 of whom were negative by RT-PCR. The difference between the two groups was statistically significant (p<0.05). These outcomes showed that the HRCT evaluation for prediction of COVID-19 sensitivity was 94.8%, specificity was 86.9%, accuracy was 93.5%, positive predictive value (PPV) was 97.5%, and negative predictive value (NPV) was 75.7%. RT-PCR is the gold-standard test for identifying COVID-19; HRCT can be useful in situations where RT-PCR is expected but COVID-19 isolation is a concern. HRCT evaluation for prediction of COVID-19 has more sensitivity and accuracy. Jalalabad Med J 2022; 19 (2): 54-59